1997
DOI: 10.3171/jns.1997.86.6.0990
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel anterior cervical corpectomy and fibular allograft fusion for cervical myelopathy

Abstract: This study was conducted to determine the safety and efficacy of multilevel anterior cervical corpectomy and stabilization using fibular allograft in patients with cervical myelopathy. Thirty-six patients underwent this procedure for cervical myelopathy caused by spondylosis (20 patients), ossified posterior longitudinal ligament (four patients), trauma (one patient), or a combination of lesions (11 patients). The mean age (+/- standard deviation) of the patients was 58 +/- 10 years and 30 of the patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(128 citation statements)
references
References 30 publications
2
121
1
2
Order By: Relevance
“…Unfortunately, details on the number of instrumented vertebra, distribution of decompressed levels, and additional usage of the Halo are often lacking. Anecdotally, construct failures in multilevel corpectomies with stand-alone strut grafts have been reported and reviewed as high as 10-50% [33,68,89,94,96,107], whereas stand-alone grafts do not support or halter the reconstructed cervical lordosis in multisegmental constructs [91]. Recently, Ikenaga et al [52] reported a 85% fusion rate after 12 months in 112 multilevel corpectomies using long fibular grafts afixed with one screw caudally.…”
Section: Clinical Failures In Multilevel Anterior Cervical Constructsmentioning
confidence: 99%
“…Unfortunately, details on the number of instrumented vertebra, distribution of decompressed levels, and additional usage of the Halo are often lacking. Anecdotally, construct failures in multilevel corpectomies with stand-alone strut grafts have been reported and reviewed as high as 10-50% [33,68,89,94,96,107], whereas stand-alone grafts do not support or halter the reconstructed cervical lordosis in multisegmental constructs [91]. Recently, Ikenaga et al [52] reported a 85% fusion rate after 12 months in 112 multilevel corpectomies using long fibular grafts afixed with one screw caudally.…”
Section: Clinical Failures In Multilevel Anterior Cervical Constructsmentioning
confidence: 99%
“…in patients with ALS, MS, normotensive hydrocephalus) and even a risk of perioperative mortality, with a major morbidity rate of up to 22%, e.g. with corpectomy [29]. Twenty-five percent of patients with laminoplasty suffer from severe neck and shoulder pain for more than 3 months [18], with significant morbidity from the iliac crest donor site etc.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of iatrogenic VA injury in anterior cervical decompression procedures has been reported to range from 0.18 to 2.78 % [1,[19][20][21][22]. James et al [19] reported that VA injury can occur if decompression is asymmetric or overly aggressive.…”
Section: Discussionmentioning
confidence: 99%